The housing market in Algeria: What state of the art? - اوكاسي, كمال (جامعة مسيلة, 2018)
Housing policy in Algeria has gradually changed, in relation with the financial imbalance recorded since 1986 and the demand of the citizens. As in most developing countries, Algeria is going through a housing crisis, fueled mainly by the acceleration of the urbanization movement; The transformation of the family structure and the accessibility difficulties for certain segments of the market. In this paper, we will try to analyze the housing market in Algeria to give elements of appreciation and understanding of the crisis in the sector, through an analysis of the evolution of supply and demand, household expenditure and the housing finance situation
Keywords: Algeria, housing market, household solvency, housing crisis Jel classification codes : R31. R21. P25